2020
DOI: 10.1021/acs.chemrev.0c00806
|View full text |Cite
|
Sign up to set email alerts
|

Click and Bio-Orthogonal Reactions with Mesoionic Compounds

Abstract: Click and bio-orthogonal reactions are dominated by cycloaddition reactions in general and 1,3-dipolar cycloadditions in particular. Among the dipoles routinely used for click chemistry, azides, nitrones, isonitriles, and nitrile oxides are the most popular. This review is focused on the emerging click chemistry that uses mesoionic compounds as dipole partners. Mesoionics are a very old family of molecules, but their use as reactants for click and bio-orthogonal chemistry is quite recent. The facility to deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 240 publications
(377 reference statements)
0
29
0
Order By: Relevance
“…357 10F), 106 which works through a [3+2] cycloaddition reaction between donor 89 and a commercially available strained cyclooctyne to achieve controllable "click-and-release" of COS/H 2 S in both PBS and live cells. 361 In vitro experimental results showed that H 2 S release from donor 89 exclusively relies on and is also dose-dependent on the strained cyclooctyne. Moreover, the fluorescence intensity and concentration of thiophene fluorophore after the activation of donor 89 are well proportional to the H 2 S yield.…”
Section: Other H 2 S Donors With Miscellaneous Releasing Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…357 10F), 106 which works through a [3+2] cycloaddition reaction between donor 89 and a commercially available strained cyclooctyne to achieve controllable "click-and-release" of COS/H 2 S in both PBS and live cells. 361 In vitro experimental results showed that H 2 S release from donor 89 exclusively relies on and is also dose-dependent on the strained cyclooctyne. Moreover, the fluorescence intensity and concentration of thiophene fluorophore after the activation of donor 89 are well proportional to the H 2 S yield.…”
Section: Other H 2 S Donors With Miscellaneous Releasing Mechanismsmentioning
confidence: 99%
“…Future studies are expected to develop highly efficient and more targeted bioorthogonal reaction‐based COS/H 2 S donation platforms 357 . Most recently, with the aid of density functional theory (DFT) calculations, Liang et al developed another bioorthogonal reaction‐based COS/H 2 S‐donation system (Figure 10F), 106 which works through a [3+2] cycloaddition reaction between donor 89 and a commercially available strained cyclooctyne to achieve controllable “click‐and‐release” of COS/H 2 S in both PBS and live cells 361 …”
Section: H2s Donors and H2s‐releasing Hybrid Moleculesmentioning
confidence: 99%
“…Recently, such efficient cycloadditions have come to the fore in bioorthogonal chemistry, [6,7] a term first introduced by Bertozzi in 2003 to cover chemical reactions that can be conducted in living systems without disrupting natural processes [8,9] . Although bioorthogonal cycloadditions are mainly exemplified by the well known azide‐alkyne click chemistry, [10–13] other 1,3‐dipoles including diazo compounds also function, sometimes at higher rates [14–20] . In continuation of our interest in the generation and reaction of diazo compounds, [21–27] we now report that diazophosphonates are particularly suitable 1,3‐dipoles in both intermolecular, and for the first time, intramolecular cycloaddition reactions with alkynes to give N ‐unsubstituted pyrazoles.…”
Section: Figurementioning
confidence: 82%
“…Biorthogonal reactions of sulfonyl sydnone imines as prodrugs and dibenzoazacyclooctyne derivatives are served as an efficient tool to release sulfonamide medications under physiological conditions. An extensive and excellent review on the synthetic and biomedical applications of bioorthogonal reactions of sydnone imines and related mesoionic compounds was very recently published [ 54 ].…”
Section: Sydnone Iminesmentioning
confidence: 99%